Current strategies to improve the efficiency and safety of prevention and treatment of embolic stroke in non-valvular atrial fibrillation: possibilities of neutralizing therapy - S. N. Yanishevsky (Неврология, нейропсихиатрия, психосоматика)
The paper reviews an update on the status of neurological care and thrombolysis in patients with ischemic stroke (IS) who take oral anticoagulants. The possibilities of providing effective and relatively safe emergency care to patients with IS, including those receiving new oral anticoagulants, are shown to be substantially expanded now. Since it is necessary for recanalization therapy to block the effect of an anticoagulant, the latter that has a specific antagonist should be prescribed as a basic therapy to prevent stroke.